REGULASI JANGKA WAKTU PENDAFTARAN HAK ATAS TANAH MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP - Fika Safitri Khaerunnisa (2021)
The implementation of the process of registering land rights through the Comprehensive Systematic Land Registration Program encountered many obstacles in terms of a long period of time. The purpose of this study is to examine legal certainty for the community regarding the Regulation of the Registration Period for Land Rights through the Complete Systematic Land Registration program. This study uses the juridical empirical legal research method, namely the juridical approach used to analyze various laws and regulations, while the empirical approach is an approach based on seeing a legal reality in society. The results show that based on the applicable legal provisions, the period of registration of land rights to the issuance of land title certificates based on Ministerial Regulation Number 6 of 2018 is 14 days, while the issuance of the certificate is 3 months, but in fact the process of issuing certificates takes time. which is quite long due to several constraints on physical data requirements and juridical data on land parcels. Accountability carried out by the East Jakarta National Land Agency regarding the duration of issuance of land title certificates by disseminating information regarding the requirements that must be completed in applying for registration of land rights, adding workers especially in the field of measurement, improving technical skills of measuring officers by following developments in measurement technology and mapping. Key words: Regulation, Registration, Land Certificate